2021
DOI: 10.1371/journal.pone.0245100
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spokesperson attribution on public health message sharing during the COVID-19 pandemic

Abstract: It is urgent to understand how to effectively communicate public health messages during the COVID-19 pandemic. Previous work has focused on how to formulate messages in terms of style and content, rather than on who should send them. In particular, little is known about the impact of spokesperson selection on message propagation during times of crisis. We report on the effectiveness of different public figures at promoting social distancing among 12,194 respondents from six countries that were severely affecte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 44 publications
4
26
1
Order By: Relevance
“…Finally, since we wanted to ensure comparability of the findings for the expert condition across topics (which we expected to perform well in softening extreme opinions), we used the same fictitious expert for all topics. In contrast to our results, a known medical expert spokesperson was found to increase the engagement of social media users for the topic of physical distancing during the early stages of the COVID-19 pandemic [2]. Thus, an investigation into the performance of different experts (including gender and ethnicity) and of real, known experts would be of interest to determine the factors that might make experts more convincing.…”
Section: Limitationscontrasting
confidence: 99%
“…Finally, since we wanted to ensure comparability of the findings for the expert condition across topics (which we expected to perform well in softening extreme opinions), we used the same fictitious expert for all topics. In contrast to our results, a known medical expert spokesperson was found to increase the engagement of social media users for the topic of physical distancing during the early stages of the COVID-19 pandemic [2]. Thus, an investigation into the performance of different experts (including gender and ethnicity) and of real, known experts would be of interest to determine the factors that might make experts more convincing.…”
Section: Limitationscontrasting
confidence: 99%
“…A large-scale survey found that "across countries and demographic strata, immunology expert Dr. Anthony Fauci achieved the highest level of respondents' willingness to reshare a call to social distancing, followed by a government spokesperson. Celebrity spokespersons were least effective" [4]. Similar results have also found independent confirmation [50].…”
Section: Scientists and The Publicsupporting
confidence: 61%
“…This sifting was done using Dimensions [67]. 4 In the case of megajournals, the author used Field of Research 5 categories to only sift through contributions not included in the Biological Sciences (division 06), Agriculture and Veterinary Sciences (division 07) or Medical and Health Sciences (division 11). At all stages, manifestly opinionated pieces which assume or strongly support personal, political or ideological views, even when published as research contributions, have not been included.…”
Section: Introductionmentioning
confidence: 99%
“…Negative opinions expressed by public figures about a vaccine could impact a large population of people, especially those who do not hold an unswayable opinion [ 48 ]. People tend to believe public figures’ opinions, as they are elected officials who can influence health care systems and are perceived to have more information about a vaccine [ 50 , 51 ]. Thus, public figures have a responsibility to disseminate accurate health information and should be cautious in expressing their opinions in public.…”
Section: Discussionmentioning
confidence: 99%